Illuminating a tadpole's metamorphosis III: quantifying past and present environmental impact. Issue 3 (25th July 2020) - Reiter, Megan; Haworth, Thomas J; Guzmán, Andrés E; Klaassen, Pamela D; McLeod, Anna F; Garay, Guido
ABSTRACT: We combine Multi-Unit Spectroscopic Explorer and Atacama Large Millimeter/sub-millimeter Array observations with theoretical models to evaluate how a tadpole-shaped globule located in the Carina Nebula has been influenced by its environment. This globule is now relatively small (radius ∼2500 au), hosts a protostellar jet+outflow (HH 900), and, with a blueshifted velocity of ∼10 km s −1, is travelling faster than it should be if its kinematics were set by the turbulent velocity dispersion of the precursor cloud. Its outer layers are currently still subject to heating, but comparing the internal and external pressures implies that the globule is in a post-collapse phase. Intriguingly the outflow is bent, implying that the Young Stellar Object (YSO) responsible for launching it is comoving with the globule, which requires that the star formed after the globule was up to speed since otherwise it would have been left behind. We conclude that the most likely scenario is one in which the cloud was much larger before being subject to radiatively driven implosion, which accelerated the globule to the high observed speeds under the photoevaporative rocket effect and triggered the formation of the star responsible for the outflow. The globule may now be in a quasi-steady state following collapse. Finally, the HH 900 YSO is likely ≳1 M⊙ and may be the only star forming in the globule. It may be that this process of triggered star formation has prevented the globule from fragmenting to form multiple stars (e.g. due to heating) and has produced a single higher mass star.